Restoring light transmission of dusty glass surfaces on the Moon. Issue 10 (15th November 2021) - Doner, A.; Horányi, M.; Faller, J.; Fontanese, J.; Munsat, T.
Abstract: The Lunar Laser Ranging Retro-reflectors (LRR) allow for the precise measurement of the travel time of laser pulses from the Earth to the lunar surface and back. Dust accumulation on the LRRs scatters the reflected light used for laser interferometry measurements leading to a reduction in the return signal amplitude by a factor of ≃ 10. We report on a series of experiments utilizing a method of an iterative application and removal of an acrylic adhesive kapton tape to remove lunar dust simulant from a glass substrate. The effectiveness of adhesive tape was determined by measuring the transmission of an expanded laser beam through a glass substrate with a dusted surface. Calibration data was obtained before the glass was exposed to any dust, and light transmission was measured after each iteration of adhesive removal using a power meter. The procedure was repeated using heavy gloves while keeping the glass substrate at 120 ° C to simulate the temperature conditions of a lunar day on the surface. A third test was conducted at room temperature in high-vacuum to ensure functionality in the lunar environment. These experiments show that glass substrates can be restored to 98 ± 2 % of their original transmission using the adhesive tape method. Therefore the light that travels into and out of the quartz surface of the LLRs can be restored up to 96 ± 4 % of their initial transmission.